Information Motivation Behavioural Skills Model and Cyberbullying Bystanders ' Behaviour to Intervene or Not Intervene - Onditi, Hezron Z (Papers in Education and Development, 2021)
Abstract Using Information Motivation Behavioural Model (IMB), this study explored peers behaviour to intervene or not for victims in cyberbullying situations. The aim is to promote further research on bystanders ' behaviour using IMB model that has been intensively used in preventive and intervention studies. The paper begins by explaining school bullying and cyberbullying as well as bystanders ' role in bullying situations. Next, a general discussion of the IMB model and how it can be applied to assess online bystanders ' motivation to intervene or not intervene in cyberbullying situations is provided. This paper concludes by illuminating the strengths and limitations of the IMB model and suggests how the framework may be applied in future studies and in developing a comprehensive theoretical model for understanding, explaining and predicting online bystanders ' behaviour. Keywords: bullying, bystanders, cyberbullying, IMB model